The Effect Of Information Asymmetry, Accounting Conservatism, And Firm Size Against Earning Management With Good Corporate Governance As Moderating Variables - Syahputri, Dwi Indri; Nawirah (UNIB Press, 2023)
This study aims to investigate the impact of information asymmetry, accounting conservatism, and firm size on earning management with the moderation of good corporate governance. The population in this study is companies in the primary consumer goods industry sector listed on the IDX in 2018-2021, and samples were selected using purposive sampling techniques and obtained from as many as 18 companies that meet the research criteria. The total data becomes 72 observational data. The data was analyzed using a panel data regression test with the help of the Eviews 12 application. The results of this study show that information asymmetry and firm size do not have a significant effect on earning management, accounting conservatism has a negative and significant impact on earning management, GCG is unable to moderate or weaken the relationship between information asymmetry, accounting conservatism and firm Size on earning management